Improvement of Mitochondrial Activity and Fibrosis by Resveratrol Treatment in Mice with Schistosoma japonicum Infection - Chen, Tina Tuwen (Biomolecules, 2019)
Schistosomiasis caused by Schistosoma japonicum is a major parasitic disease in the People’s Republic of China. Liver fibrosis is the main pathological mechanism of schistosomiasis, and it is also the major lesion. The common drug used for its treatment, praziquantel (PZQ), does not have a marked effect on liver fibrosis. Resveratrol (RSV), which is an antioxidant, improves mitochondrial function and also attenuates liver fibrosis. The combination of PZQ and RSV has been found to have a synergistic antischistosomal effect on Schistosoma mansoni; additionally, the activity of PZQ is enhanced in the presence of RSV. Here, we examine the therapeutic effects of RSV on the S. japonicum infection in a mouse model, and we investigate RSV as a novel therapeutic agent for mitochondrial function and schistosomiasis-associated liver fibrosis (SSLF). Mitochondrial membrane potential was examined using flow cytometry analysis. The expression of the mitochondrial biogenesis genes PGC-α and fibrosis-associated genes collagen I, collagen III and α-SMA were examined using western blot analysis. Fibrosis-associated histological changes were examined using Masson trichrome staining. Additionally, the effects of RSV on S. japonicum adult worms were examined using scanning electron microscopy and transmission electron microscopy. RSV treatment improved mitochondrial function by increasing membrane potential and increasing PGC-α expression (mitochondrial biogenesis). Further, RSV attenuated liver injury, including liver scarring, by decreasing collagen deposition and the extent of fibrosis, based on the decrease in expression of the fibrosis-related genes. RSV also decreased the adult worm count and caused considerable physical damage to the worm. These results indicate that RSV upregulates mitochondrial biogenesis and inhibits fibrosis. RSV may have potential as a therapeutic target for the treatment of fibrosis in schistosomiasis.